Climate change impact on medicinal plants in Indonesia - Cahyaningsih, Ria; Phillips, Jade; Magos Brehm, Joana; Gaisberger, Hannes; Maxted, Nigel (Elsevier, 2021)
Indonesia is a global hotspot of plant diversity. The country contains medicinal plants that have immense value to the people and worldwide. However, climate change is affecting the distribution of medicinal plants in Indonesia. In this study, the future greenhouse gas emission scenarios of RCP4.5 and RCP8.5 for a mid-term future projection to 2050 and a long-term future projection to 2080 were used to simulate the effect of climate change upon medicinal plants distribution within Indonesia. In 2050 and 2080, under both RCP scenarios species richness is expected to decrease over more than half the current distribution area of medicinal plant species. Over half of the medicinal plant species populations will lose up to 80% of their distribution area. Medicinal plant species on the islands of Papua, Java, and Sulawesi are predicted to have the largest reduction in distribution area. In addition, two-thirds of species will lose rather than gain areas of suitable climate under the future climate scenarios. Twenty medicinal plant species are identified as potentially being the most threatened by climate change in the future and are therefore the highest priority for conservation actions within Indonesia. Using these results, we recommend areas and species suitable for long term in situ and ex situ conservation within Indonesia.